Transition risks and market failure: a theoretical discourse on why financial models and economic agents may misprice risk related to the transition to a low-carbon economy. (2nd January 2017) - Thomä, Jakob; Chenet, Hugues
ABSTRACT: This paper provides a theoretical discourse linking traditional market failure literature and the recent research around potential stranded assets risks associated with the transition to a low-carbon economy (defined here as 'transition risks'). While it does not seek to prove a mispricing in practical terms, it demonstrates the extent to which the market failure literature provides theoretical evidence of a potential mispricing of these risks, as a result of the design and interpretation of financial risk models, and the practices and institutions linked to economic agents. The evidence supports a growing body of practical literature highlighting transition risks in financial markets. It suggests that there may be a case for policy intervention to address the market failures and associated potential mispricing of risk. It also suggests however that this intervention will likely need to address both the design of financial risk models and associated transparency around their results, and the actual institutions governing risk management. A key challenge in this regard involves resolving the principal–agent problem in financial markets and the associated 'tragedy of the horizons'.